Biodegradation and Bioaccumulation Rate of PCBs in Cows - Kareem Mohammed, Alaa (Journal of Engineering and Sustainable Development, 2012)
The object of this research is to focus on bioaccumulation and biodegradation rate of hydrophobic, persistent pollutants namely PCBs in cows. A simple mathematical mass balance equation which represents the input and output streams of these persistent pollutants to a cow was developed. Samples were taken from rural agricultural farms in Abu-Greab in Baghdad. These samples were analyzed for input and output terms which represent vegetation, soil, concentrate, milk and feces to measure the concentration of PCBs in these samples. It was found that bioaccumulation and biodegradation rate of PCBs in cows is a bout 202.6 µg/d. and most of PCBs input the cow is by vegetation rather than concentrate or soil while PCBs input to the cow by air or water are very low values and can be neglected so as the PCBs out put the cow by urine and air. Also it was found that the output PCBs from the cow is about 62.5% by milk and 37.5% by feces.